Adenovirus mediated p53 tumour suppressor gene therapy for human gastric cancer cells in vitro and in vivo. Issue 3 (1st March 1999) - Ohashi, M; Kanai, F; Ueno, H; Tanaka, T; Tateishi, K; Kawakami, T; Koike, Y; Ikenoue, T; Shiratori, Y; Hamada, H; Omata, M
Abstract : BACKGROUND/AIMS: Gastric cancer is one of the most prevalent forms of cancer in East Asia. Point mutation of the p53 gene has been reported in more than 60% of cases of gastric cancer and can lead to genetic instability and uncontrolled cell proliferation. The purpose of this investigation was to evaluate the potential of p53 gene therapy for gastric cancer. METHODS: The responses of human gastric cancer cell lines, MKN1, MKN7, MKN28, MKN45, and TMK-1, to recombinant adenoviruses encoding wild type p53 (AdCAp53) were analysed in vitro. The efficacy of the AdCAp53 treatment for MKN1 and MKN45 subcutaneous tumours in nude mice was assessed in vivo. RESULTS: p53-specific growth inhibition was observed in vitro in two of four gastric cancer cell lines with mutated p53, but not in the wild type p53 cell line. The mechanism of the killing of gastric cancer cells by AdCAp53 was found, by flow cytometric analysis and detection of DNA fragmentation, to be apoptosis. In vivo studies showed that the growth of subcutaneous tumours of p53 mutant MKN1 cells was significantly inhibited by direct injection of AdCAp53, but no significant growth inhibition was detected in the growth of p53 wild type MKN45 tumours. CONCLUSIONS: Adenovirus mediated reintroduction of wild type p53 is a potential clinical utility in gene therapy for gastric cancers.